Correlação do IDEB 2015 com os indicadores educacionais: a situação atual das unidades federativas do Brasil - Riscal, José Reinaldo (2020)
The present work continues the research developed in my master's degree, entitled Mapeamento Quantitativo dos Impactos da Gestão Democrática no Desempenho das Escolas Públicas no Ideb 2013. Since we observed that the vast majority of Federation Units have not been able to achieve the goals set by INEP for Elementary School II, it was decided to expand the master's project to identify which factors have the greatest impact on achieving the targets set to public schools. The objective of the doctorate project are: 1. to statistically determine the impact of educational indicators, profile characteristics of school principals and democratic management practices (in particular, the elaboration of the Pedagogical Political Project and the role of the School Councils in the administrative, fiscal and pedagogical dimensions) on the values of IDEB and on the fulfillment of the goals set by INEP for public schools, establishing the hierarchy of relative importance of these variables. 2. map the configurations of these variables in each of the Federation Units. To achieve these objectives, a documentary and statistical analysis were made with official indicators, from INEP (National Institute of Educational Studies and Research Anísio Teixeira), PDDE (Programa Dinheiro Direto na Escola, from the Ministry of Education) and IBGE (Brazilian Institute of Geography and Statistics), referring to the year 2015. The study proved that the following variables: constant participation of the School Councils in the pedagogical, fiscal and administrative decisions of the school, the permanence of the school principal for a period of not less than five years in the same school, holding a postgraduate course by the principal (specialization, master's or doctorate), exclusive dedication to school management and being chosen through a selection process have a significant impact on IDEB's values: the Federation Units with greater proportions of public schools with these characteristics tend to perform better. All of them contribute to the fulfillment of the goals of the Initial Series, while the choice of the director through a selection process, holding a postgraduate course are those that have significant contribution to the fulfillment of the goals of the Final Series. However, the modeling also showed that the chance of achieving the targets is inversely proportional to the initial value of IDEB in 2005, which shows that the Federation Units that performed better in the first wave of the index were penalized with more aggressive targets.